Refractory diabetes insipidus following drainage of chronic subdural haematoma. (August 2013) - Won, Yu Deok; Kim, Choong Hyun; Cheong, Jin Hwan; Kim, Jae Min
Abstract Background: Post-traumatic diabetes insipidus (DI) is a relatively common complication after head injury. The authors report a fatal case of refractory DI, which developed in a patient with chronic subdural haematoma. Case history: A 38-year-old woman presented to the emergency room with a headache for over a week. She was alert and neurological examination demonstrated no significant deficits or external wounds in her head. Brain computed tomography (CT) scans revealed a small amount of chronic subdural haematoma bilaterally. She was treated conservatively and her hospital course was uneventful until she developed a convulsive seizure and mental change on the 3rd day after admission. Immediate follow-up CT scans showed no significant change in the amount of haemorrhage except effacement of gyral marking. Bilateral trephination and drainage of the haematoma were performed immediately. Post-operatively, she developed a refractory DI and was managed in the intensive care unit. However, she died on the 6th day after the operation ultimately. Conclusion: The authors emphasize the importance of timely drainage of chronic subdural haematoma to prevent a fatal endocrinologic complication after head injury. This study also discusses the possible mechanism of DI after head injury, management and review of the pertinent literatures.